Helping Children with Special Needs: Who Receives Tympanostomy Tubes?. (August 2021) - Wassef, David W.; Dhaduk, Nehal; Roy, Savannah C.; Barinsky, Gregory L.; Kalyoussef, Evelyne
Objectives: Tympanostomy tubes can prevent sequelae of otitis media that adversely affect long term hearing and language development in children. These negative outcomes compound the existing difficulties faced by children who are already diagnosed with developmental disorders. This study aims to characterize this subset of children with developmental disorders undergoing myringotomy and tympanostomy tube insertion. Methods: A retrospective review using the Kids' Inpatient Database (KID) was conducted, with codes from International Classification of Diseases, Ninth Revision used to query data from the years 2003 to 2012 to determine a study group of children with a diagnosis of a developmental disorder undergoing myringotomy and tympanostomy insertion. This group was compared statistically to patients undergoing these procedures who did not have a diagnosed developmental disorder. Results: In total, 21 945 cases of patients with myringotomy with or without tympanostomy tube insertion were identified, of which 1200 (5.5%) had a diagnosis of a developmental disorder. Children with developmental disorders had a higher mean age (3.3 years vs 2.9 years, P  = .002) and higher mean hospital charges ($43 704.77 vs $32 764.22, P  = .003). This cohort also had higher proportions of black (17.6% vs 12.3%, P  < .001) and Hispanic (23.9% vs 20.6%, P  = .014) patients, and had lower rates of private insurance coverage (39.6% vs 49%, P  < .001). Conclusion: The population of children with developmental disorders undergoing myringotomy or tympanostomy tube placement has a different demographic composition than the general population and faces distinct financial and insurance coverage burdens. Further study should be done to assess if these differences impact long term outcomes.